2020
DOI: 10.1186/s40463-020-00405-w
|View full text |Cite
|
Sign up to set email alerts
|

Can drug-induced sleep endoscopy improve the success rates of tongue base surgery?

Abstract: Background: The purpose of this study was to determine the therapeutic value of drug-induced sleep endoscopy (DISE) by comparing the outcomes of tongue base surgery based on Muller's maneuver (MM) and those based on DISE in obstructive sleep apnea (OSA) patients. Methods: Ninety-five patients who underwent the tongue base surgery in combination with palatal surgery for OSA at a tertiary referral hospital between March 2012 and March 2019 were enrolled in this retrospective comparative study. Forty-seven patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 26 publications
(33 reference statements)
1
19
0
Order By: Relevance
“…5 Many studies have been published describing patterns of obstruction observed during DISE and associations with baseline OSA severity. 6-9 In addition, there is a growing body of literature describing the impact of DISE on treatment decision making in adult OSA 10-13 and the utility of DISE in predicting surgical outcomes. 14-17…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Many studies have been published describing patterns of obstruction observed during DISE and associations with baseline OSA severity. 6-9 In addition, there is a growing body of literature describing the impact of DISE on treatment decision making in adult OSA 10-13 and the utility of DISE in predicting surgical outcomes. 14-17…”
mentioning
confidence: 99%
“…5 Many studies have been published describing patterns of obstruction observed during DISE and associations with baseline OSA severity. [6][7][8][9] In addition, there is a growing body of literature describing the impact of DISE on treatment decision making in adult OSA [10][11][12][13] and the utility of DISE in predicting surgical outcomes. [14][15][16][17] The widespread utilization of DISE by sleep surgeons and the significant advances that have been made in DISE-related research have led to increased convergence in the practice of adult DISE.…”
mentioning
confidence: 99%
“…Recent studies have reported that the surgical plan based on examination of awake patients changed after DISE in 40–50% of patients [ 27 , 28 ]. Improving success rates of sleep surgery [ 29 , 30 ] affects decision making [ 31 ] especially if the tongue was involved; however, there was a lack of evidence regarding the superiority of DISE over Müller’s maneuver with respect to surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the epiglottis has reduced its swelling and the AHI has improved significantly after 6 months of medical therapy with alginate. There are countless other potential explanations for the differences between the two sleep studies and the two DISE studies [ 22 , 23 ]. However, all of them were exhaustively excluded although retrospectively these factors could be confounding ones: there were no concurrent URTI, the patient does not smoke nor is vaping nor in alcohol use.…”
Section: Discussionmentioning
confidence: 99%